ANALISIS RASIO LANCAR RUMAH SAKIT X - Marsdenia, Marsdenia (UI Scholars Hub, 2013)
Increasing the efficiency of hospital management sustainability is an ongoing financial management guidelines that absolutely must be adopted by any hospital. This study aims at obtaining information about the components that contribute to the fluctuations of the current ratio Hospital X between 2000, 2001 and 2002. This study used quantitative and qualitative approaches, with the primary data source (in-depth interviews to the relevant parties ie Hospital Director, Chief Financial Officer and Vice Director Adiministrasi Finance) and the secondary data source include financial statements. The research shows that RS X’s current ratio are still in a normal range except in the year of 2001 was below the standard (1.42). The more sensitive ratio, Acid Test Ratio, is still in normal range in the year of 2000, but in the year of 2001, and 2002, the ratios are in the lowest bend of the normal range. Cash Ratios for many years are also in the lowest bend except for the year of 2000, Receivable turn over ratios for the last three years go smaller showing that receivables took longer time to collect, the normal range for receivable turn over is 14 up to 20 days. Inventory turn over ratios are below the standard range (24-32 times per year), the average inventory held in warehouse is between 16 up to 21 days. The value of current ratio is got from comparison between current assets and current liabilities. Nominally, RS X’s current ratio in 2002 is in the state bend, namely, 1.5 – 2.00, in the real term, the ratio shows on contradictory pictures. The reasons are a) Guaranteed Receivables are valued above the normal practice (overstated) b) overstated of Non Guaranteed receivables/Personal Receivables. Based on this research, the author thinks that there are some rooms for RS X’s management to fit their current ratio problem. There are several suggestions that the management can adopt, namely controlling cash outflow and cash inflow, reevaluating receivables policy, reforming the supply of inventories (medicine) procedures.